Metadata for the energy performance certificates of buildings in smart cities - Baptista, Ana Alice (2017)
SusCity is a MIT Portugal project that falls within the scope of smart cities. One of its tasks aims to research and develop metadata artefacts to be used in the scope of a Linked Open Data platform. In this article, we report the process and results associated with the development of the following metadata artefacts: an application profile, a metadata schema and four controlled vocabularies. The application field is the energy certification of buildings. For the development of the application profile, we inspired ourselves in the Me4MAP method although we did not use it thoroughly. The creation of the metadata schema and controlled vocabularies involved the use of Wikidata, so all new terms (RDFS classes and properties and SKOS concepts) are related to Wikidata terms. The results include the application profile, the metadata schema and the controlled vocabularies. The application profile has 13 properties, four of which are new. The controlled vocabulary on measures for energy performance has 22 new terms spread over four levels. The remaining controlled vocabularies just hold a few terms each. All the artefacts are open to the community for use and reuse.